Knygotyros spaudiniai Vaclovo Biržiškos asmeninėje bibliotekoje - Raguotis, Bronius (Knygotyra, 1996)
The well-known bibliographer and historian of press Vadovas Biržiška (1884-1956) has addressed the problems of books' and periodicals' distribution and their functioning in many of his works.This researcher was particularly interested in the transportation and distribution of Lithuanian books and periodicals during the abolition of Lithuanian publishing (1864-1904). Lithuanian publications in Latin script were banned and persecuted by the authorities of the Russian Empire. Therefore, they were published abroad and secretly transported to Lithuania.The author of the article analyzes the issues of the publications' distribution in V. Biržiška's works. V. Biržiška has paid much attention to the periodization of book carrying, the motivation of the activities of book traders and transporters, and the cooperation of the Russian and German authorities in the persecution of those distributing the banned literature.The issues that V. Biržiška raised were further explored, developed, and dealt with by Lithuanian historians of later periods.